Chondrosarcoma of the thyroid cartilage: surgical management of a rare case. Issue 1 (17th January 2023) - Kinsella, Anna; Corbett, Mel; Hacking, Sean; Lang, John
Abstract : Laryngeal malignancy encompasses about 1% of all cancers. Chondrosarcoma in the head and neck region represents about 0.1% of head and neck malignancies. Typical presenting symptoms relate to the anatomical location of these tumours and include dysphonia, inspiratory stridor, dysphagia, odynophagia or a neck mass. Benign and malignant cartilaginous cancers of the larynx have been described, and preoperative diagnosis can be difficult. Our report highlights the surgical management of a male patient in his 50s with chondrosarcoma of the thyroid cartilage.